Sistem Informasi Manajemen Data Sekolah Berbasis Website - Siti Sufaidah; Luqman Nuur Huda (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to design and implement a web-based school data management system at Al-Husna Islamic Kindergarten to address the problems of semi-manual recording that often results in data duplication, recording errors, and delays in information delivery. The development method used is the Waterfall method with stages of needs analysis, design, implementation, testing, and maintenance. Research data was obtained through observation and interviews with the school to identify system requirements. The result of this study is a web-based school management information system that facilitates the management of student data, teacher data, lesson schedules, school agendas, and recording teacher assignments. Testing using the blackbox method shows that all functions run according to user needs. With this system, the data management process at Al-Husna Islamic Kindergarten becomes more effective, efficient, and supports school operational activities.